2017
DOI: 10.18632/oncotarget.17648
|View full text |Cite
|
Sign up to set email alerts
|

ADAM9 enhances CDCP1 by inhibiting miR-1 through EGFR signaling activation in lung cancer metastasis

Abstract: MicroRNAs (miRNAs), which are endogenous short noncoding RNAs, can regulate genes involved in important biological and pathological functions. Therefore, dysregulation of miRNAs plays a critical role in cancer progression. However, whether the aberrant expression of miRNAs is regulated by oncogenes remains unclear. We previously demonstrated that a disintegrin and metalloprotease domain 9 (ADAM9) promotes lung metastasis by enhancing the expression of a pro-migratory protein, CUB domain containing protein 1 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…Chiu showed that ADAM9 downregulated the miR-1 expression via activating the EGFR signaling pathways, which in turn enhanced CDCP1 expression to promote lung cancer progression. 31 Coincidentally, in our present study, we proposed a putative miR-1-3p binding on RMRP ( Figure 4A), which triggered us to ask whether RMRP-miR-1-3p could be a tumorrepressor axis in NSCLC samples. By dual-luciferase reporter assay, we found that miR-1-3p mimics suppressed the luciferase intensity of only RMRP-WT but not RMRP-MT ( Figure 4B), indicative of the specific binding of miR-1-3p with RMRP.…”
Section: Discussionsupporting
confidence: 49%
“…Chiu showed that ADAM9 downregulated the miR-1 expression via activating the EGFR signaling pathways, which in turn enhanced CDCP1 expression to promote lung cancer progression. 31 Coincidentally, in our present study, we proposed a putative miR-1-3p binding on RMRP ( Figure 4A), which triggered us to ask whether RMRP-miR-1-3p could be a tumorrepressor axis in NSCLC samples. By dual-luciferase reporter assay, we found that miR-1-3p mimics suppressed the luciferase intensity of only RMRP-WT but not RMRP-MT ( Figure 4B), indicative of the specific binding of miR-1-3p with RMRP.…”
Section: Discussionsupporting
confidence: 49%
“…This ADAM9-CDCP1 axis to lung cancer metastasis is also validated in several other reports as well [ 92 , 93 ]. The ADAM9-CDCP1 axis was confirmed to be necessary for lung cancer cell migration and survival in vitro and in vivo; and moreover, the authors demonstrated that ADAM9 decreases the expression of miR-1 and miR-218, which target the 3′-UTR of CDCP1 to suppress its expression.…”
Section: Role Of Adam9 In Cancerssupporting
confidence: 79%
“…Many miRNAs have been reported down‐regulated in lung cancer, such as miR‐34b/c, miR‐1, miR‐206, miR‐145 and let 7 . Among them, miR‐1‐3p and miR‐206, which belong to muscle‐specific miRNAs and play key roles in skeletal muscle differentiation, have found exhibited inhibitory function in lung cancer growth, migration and invasion in recent years . However, other functions of these two miRNAs are not known.…”
Section: Discussionmentioning
confidence: 99%